Effect of Modified Kepok Banana Starch Substitution on Resistant Starch Content, Amylose Content, And Moisture Content of Caramel Cake - Pramitajati, Indah; Sofyan, Aan (Media Gizi Indonesia, 2026)
Modified kepok banana starch is a starch derivative product produced through an autoclaving-cooling modification process. Caramel cake substituted with modified kepok banana starch can be used as a functional food because it has bioactive compounds such as resistant starch which is beneficial for health. The aim of this study was to determine the effect of modified kepok banana starch substitution on resistant starch content, amylose content, and moisture content of caramel cake. The research method used was experimental research using a completely randomized design with 4 treatments of modified kepok banana starch substitution, namely 0%, 20%, 40%, and 60%. The multienzyme method was used to measure the resistant starch content, the spectrophotometric method was used to measure the amylose content, and the thermogravimetric method was used to measure the moisture content. Data analysis used the One Way Anova test for resistant starch and amylose content, as well as the Kruskal Wallis test for moisture content. The results of the analysis of the lowest resistant starch content was 6.25% with treatment P2 (20%), while the highest content was 8.00% with treatment P4 (60%). The resistant starch content showed a p value = 0.00. The lowest amylose content was 1.29% with treatment P4 (60%), while the highest content was 2.53% with treatment P2 (20%). The amylose content showed a p value = 0.00. The lowest water content was 32.85% with treatment P4 (60%), while the highest content was 38.45% with treatment P1 (0%).